Fierce Communal Riots in the Novel the Rape by Raj Gill: Unveiling the Horrors of Communal Violence in Raj Gill's Novel (Journal of Advances and Scholarly Researches in Allied Education, 2018)
Raj Gill in his novel The Rape records the fierce communal riots, the inhuman atrocities, the burning down of villages and the massive killing of the people, the three month-long communal violence in Gurgaon, the pitched battles in the different parts of the Punjab, the firing of the troops, the massacre of the Sikhs and Hindus in Rawalpindi and Multan and the innumerable cruelties perpetrated by people out of sheer communal frenzy. It relates the horrors of the chopping off women’s breasts and the shameful scene of nude women leading the Muslim procession. Dalipjit did not find anything to celebrate on the day of the transfer of power; he only felt that ‘the red-faced monkies’ have been substituted by ‘the black-faced lemur’ to continue the chain of slavery for the people.